Maize Germination: Trends and The Impact of Microbial Factors on Growth and Nutrient Uptake - Saleem, Muhammad; Hassan, Samia; Ihsanullah, Muhammad; Ibrahim, Sadia; Hashim, Muhammad Naveed; Muhammad Imran; Sani, Imran Ali; Khalid, Talha; Uzair, Muhammad Usama; Raza, Ahmad (Indus Journal of Bioscience Research, 2025)
Corn (Zea mays) is essential to global food security, especially in nutrient-poor soils. Interactions with microbes, including plant growth-promoting rhizobacteria (PGPR) and arbuscular mycorrhizal fungi (AMF), boost nutrient absorption and crop yield. Nevertheless, the exact mechanisms by which microbial communities influence corn germination and development remain poorly understood. This study examined the influence of microbial inoculation on corn germination, nutrient uptake, and productivity to address knowledge gaps in plant-microbe interactions and their relevance to sustainable farming practices. In conjunction with field studies, a controlled experiment was conducted to assess microbial consortia’s impact on corn. Seeds were inoculated with PGPR and AMF, and their performance was measured against untreated controls. Nutrient absorption was evaluated through elemental analysis of plant tissues, and growth parameters were recorded across the treatment groups. Statistical evaluation included ANOVA and Tukey’s post-hoc tests to verify the significance of the observed differences. The findings revealed a marked improvement in germination rates (93% vs. 78%), nutrient uptake (34% increase in nitrogen, 28% in phosphorus, and 21% in zinc), and yield metrics (22% increase in cob weight and 24% increase in overall yield) in inoculated groups compared to controls. Elevated enzyme activities in the rhizosphere, including phosphatase and nitrogenase activities, supported the observed enhancements. This investigation underscores the potential of microbial consortia as a bioinoculant to enhance corn productivity. These results offer valuable insights for incorporating microbial strategies into sustainable agricultural methods, particularly in nutrient-deficient soils. Subsequent research should focus on exploring diverse microbial communities and their long-term ecological effects.